1993
DOI: 10.1128/aac.37.12.2618
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic enzymes: a new treatment strategy for prosthetic infections?

Abstract: Among the different mechanisms of bacterial resistance to antimicrobial agents that have been studied, biofilm formation is one of the most widespread. This mechanism is frequently the cause of failure in the treatment of prosthetic device infections, and several attempts have been made to develop molecules and protocols that are able to inhibit biofilm-embedded bacteria. We present data suggesting the possibility that proteolytic enzymes could significantly enhance the activities of antibiotics against biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 17 publications
0
51
0
Order By: Relevance
“…A great effort has been made to develop antipathogenic drugs and strategies (29,57,61), especially by means of reducing bacterial virulence through intercellular communication (QS). Blocking of QS in P. aeruginosa by the use of QSIs has been shown to be a promising strategy for the treatment of infections (29,49), and a series of QSIs has been identified by different groups through traditional methods (29,42,50,62).…”
Section: Discussionmentioning
confidence: 99%
“…A great effort has been made to develop antipathogenic drugs and strategies (29,57,61), especially by means of reducing bacterial virulence through intercellular communication (QS). Blocking of QS in P. aeruginosa by the use of QSIs has been shown to be a promising strategy for the treatment of infections (29,49), and a series of QSIs has been identified by different groups through traditional methods (29,42,50,62).…”
Section: Discussionmentioning
confidence: 99%
“…Chaignon et al (2007) showed that the enzymatic detachment of staphylococcal biofilms depends on the nature of their constituents and varies between clinical isolates; they tested the effect of different enzymes on biofilms and suggested a complex mixture of dispersin B and a protease (like trypsin) to remove the biofilms of a variety of staphylococcal strains. Other in vitro studies showed that proteolytic enzymes (Selan et al 1993) or lysostaphin (Walencka et al 2005;Walencka et al 2006) could significantly enhance the activities of antibiotics against biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…This probably suggests that enzymes increase the cure rate by breaking down pus, clot and fibrin and by clearing the milk duct and without any effect on biofilm. Some investigators showed that the use of enzyme is not useful in the planktonic condition of growth (Selan et al 1993;Johansen et al 1997;Berg et al 2001;Kaplan et al 2004). We evaluated biofilm formation capacity outside of the mammary gland; obviously, our in vitro conditions may differ from the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…We assayed seminal plasma 90K/MAC-2BP in 50 infertile male patients in whom diagnosis of male accessory gland infection was made according to standardized criteria and in 30 controls without male accessory gland infection and with normal sperm parameters. Assays were also performed in patients after 1-6 cycles of treatment with levofloxacin 500 mg, a fluoroquinolone whose efficacy on microbiologic eradication rates is known (Bundrick et al, 2003), plus serratiopeptidase, a 50.6-kd metalloprotease that demonstrates strong proteolytic activity enhancing the penetration of antibiotics in infected sites (Yamazaki et al, 1967) and enhancing the activity of quinolones against the development of bacterial biofilms (Selan et al, 1993), while in controls seminal 90K was reevaluated after 2 months.…”
Section: Discussionmentioning
confidence: 99%